Analisis Kemampuan Membaca Lancar Level 3 - Gentis Ayu Wariyanti; Chandra Chandra; Inggria Kharisma (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the fluent reading ability of level 3 elementary school students in grade 3 through the aspects of pauses, intonation, expression, and understanding of the text content. The approach used is qualitative with a question and answer method. Five students read the text